2013
DOI: 10.1007/s11434-012-5596-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vegetation height and density on soil temperature variations

Abstract: Reduction in vegetation cover caused by human activities has a great impact on soil temperature. It is important to assess how soil temperature responds to reduction of vegetation height and density. In this paper we first report the trends of mean annual soil surface and air temperatures recorded at the meteorological stations near the Ecological Research Station for Grassland Farming (ERSGF) from 1961 to 2007, then we setup an experiment using reed (Phragmites australis) stalks with different heights and den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 20 publications
1
37
1
Order By: Relevance
“…Of course, the highest of the three temperatures tested (i.e. 37°C) within the present investigation does not represent standard soil temperatures but might be possible in soils under certain conditions as especially the upper soil layers easily heat up in summer and can reach high temperatures (Song et al 2013). A further idea behind applying higher temperatures was to reach a temperature range more suitable for methanogens (Le Mer and Roger 2001) and -in combination with psychrophilic and mesophilic temperatures-to investigate quite great temperature steps which should indicate the direction of temperature caused effects.…”
Section: Discussionmentioning
confidence: 82%
“…Of course, the highest of the three temperatures tested (i.e. 37°C) within the present investigation does not represent standard soil temperatures but might be possible in soils under certain conditions as especially the upper soil layers easily heat up in summer and can reach high temperatures (Song et al 2013). A further idea behind applying higher temperatures was to reach a temperature range more suitable for methanogens (Le Mer and Roger 2001) and -in combination with psychrophilic and mesophilic temperatures-to investigate quite great temperature steps which should indicate the direction of temperature caused effects.…”
Section: Discussionmentioning
confidence: 82%
“…None of the models appeared to capture the slightly higher Δ T surf seen in the observational data from grassland sites as compared to forested sites (Figures a and a). Field studies have shown substantial differences in Δ T surf as a result of land cover (Beltrami & Kellman, ; Nitoiu & Beltrami, ; Song et al, ). Grassland sites tended to have a higher Δ T surf than the forested sites in our observation data set (Figure a).…”
Section: Discussionmentioning
confidence: 99%
“…A consensus is that tree canopies modify water and energy balances below them by intercepting rainfall and solar radiation. Thus, temperatures have usually been considered to be lower below tree canopies than in grasslands in summer, and the opposite in winter [8,[10][11][12]. Conversely, the influence of vegetation cover on soil water content has been a more controversial issue since it has been found to be lower under tree crowns than in grasslands in drylands and humid lands, although opposite results have also been observed [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%